Acenaphthenoannulation Induced by the Dual Lewis Acidity of Alumina - Akhmetov, Vladimir; Feofanov, Mikhail; Ruppenstein, Cordula; Lange, Josefine; Sharapa, Dmitry; Krstic, Marjan; Hampel, Frank; Kataev, Evgeny; Amsharov, Konstantin (Chemistry - A European Journal, 2022)
We have discovered a dual (i. e., soft and hard) Lewis acidity of alumina that enables rapid one-pot pi-extension through the activation of terminal alkynes followed by C-F activation. The tandem reaction introduces an acenaphthene fragment - an essential moiety of geodesic polyarenes. This reaction provides quick access to elusive non-alternant polyarenes such as pi-extended buckybowls and helicenes through three-point annulation of the 1-(2-ethynyl-6-fluorophenyl)naphthalene moiety. The versatility of the developed method was demonstrated by the synthesis of unprecedented structural fragments of elusive geodesic graphene nanoribbons.
CRIS-Team WoS Importer:2022-05-06

Anthracene-Based Amido-Amine Cage Receptor for Anion Recognition under Neutral Aqueous Conditions - Morozov, Boris S.; Namashivaya, Siva S. R.; Zakharko, Marina A.; Oshchepkov, Aleksandr S.; Kataev, Evgeny (ChemistryOpen, 2019)
A new amido-amine cage receptor, which combines 1,8-anthracene diacarboxamide subunit and a polyammonium azamacrocycle, is reported. Bearing both the hydrogen bond donor and the acceptor binding sites, the receptor is able to bind phosphate selectively under neutral (pH 7.2) aqueous conditions. The recognition events for phosphate and dicarboxylates are accomplished by a fluorescence enhancement in the anthracene emission. As revealed by experimental and theoretical studies, phosphate and oxalate show different recognition modes. Phosphate demonstrates hydrogen bond acceptor properties, while the coordination of oxalate favours the protonation of the receptor.
CRIS-Team WoS Importer:2019-12-13

Anthracene-Based Receptors with a Turn-on Fluorescence Response for Nitrate - Namashivaya, Siva S.R.; Oshchepkov, Aleksandr S.; Ding, Hui; Förster, Sebastian; Khrustalev, Victor N.; Kataev, Evgeny (Organic Letters, 2019)
Herein we describe the design, synthesis, and anion binding properties of bicyclic receptors with two or three anthracenes, which show a turn-on fluorescence response in the presence of nitrate and chaotropic anions in a buffered aqueous solution. The receptor with two anthracenes binds nitrate with 103 M-1 affinity and stabilizes it in the inner cavity though electrostatic, hydrogen bonding, and anion-πinteractions.
CRIS-Team Scopus Importer:2019-10-22

Autofluorescent Artemisinin-Benzimidazole Hybrids via Organo-Click Reaction: Study of Antiviral Properties and Mode of Action in Living Cells - Herrmann, Lars; Hahn, Friedrich; Grau, Benedikt; Wild, Markus; Niesar, Aischa; Wangen, Christina; Kataev, Evgeny; Marschall, Manfred; Tsogoeva, Svetlana (Chemistry - A European Journal, 2023)
Drug modification by a fluorescent label is a common tool for studying its mechanism of action with fluorescence microscopy techniques. However, the attachment of a fluorescent label can significantly alter the polarity, solubility, and biological activity of the investigated drug, and, as a result, the studied mechanism of action can be misrepresented. Therefore, developing efficient drugs, which are inherently fluorescent and can be tracked directly in the cell is highly favorable. Here an easy formation of fluorescent hybrid drugs is presented, generated by a combination of two readily available non-fluorescent pharmacophores via a non-cleavable linker using a Ramachary-Bressy-Wang organocatalyzed azide-carbonyl [3+2] cycloaddition (organo-click) reaction. All newly prepared fluorescent compounds showed strong anti-HCMV activity (EC50 down to 0.07±0.00 μM), thus presenting a very promising drug developmental basis compared to the approved drug ganciclovir (EC50 2.60±0.50 μM). Remarkably, in vitro fluorescent imaging investigation of new compounds revealed induced changes in mitochondrial structures, which is a phenotypical hallmark of antiviral activity. This approach opens up new vistas for the easy formation of potent fluorescent drugs from readily available non-fluorescent parent compounds and might facilitate insight into their mode of action in living cells, avoiding the requirement of linkage to external fluorescent markers.
CRIS-Team Scopus Importer:2023-09-08
Keywords: artemisinin-benzimidazole hybrids; autofluorescent antivirals; confocal microscopy; organo-click reaction; [3+2] cycloaddition

Binding and Sensing Properties of a Hybrid Naphthalimide-Pyrene Aza-Cyclophane towards Nucleotides in an Aqueous Solution - Agafontsev, Aleksandr M.; Oshchepkov, Aleksandr S.; Shumilova, Tatiana A.; Kataev, Evgeny (Molecules, 2021)
Selective recognition of nucleotides with synthetic receptors is an emerging direction to solve a series of nucleic acid-related challenges in biochemistry. Towards this goal, a new aza-cyclophane with two different dyes, naphthalimide and pyrene, connected through a triamine linker has been synthesized and studied for the ability to bind and detect nucleoside triphosphates in an aqueous solution. The receptor shows Foerster resonance energy transfer (FRET) in fluorescence spectra upon excitation in DMSO, which is diminished dramatically in the presence of water. According to binding studies, the receptor has a preference to bind ATP (adenosine triphosphate) and CTP (cytidine triphosphate) with a "turn-on" fluorescence response. Two separate emission bands of dyes allow one to detect nucleotides in a ratiometric manner in a broad concentration range of 10-5-10-3 M. Spectroscopic measurements and quantum chemical calculations suggest the formation of receptor-nucleotide complexes, which are stabilized by dispersion interactions between a nucleobase and dyes, while hydrogen bonding interactions of nucleobases with the amine linkers are responsible for selectivity.
CRIS-Team Scopus Importer:2021-03-26
Keywords: cyclophane; fluorescent probe; host–guest chemistry; nucleotide recognition; supramolecular recognition

Control of Photoisomerization of an Azoazacryptand by Anion Binding and Cucurbit[8]uril Encapsulation in an Aqueous Solution - Oshchepkov, Aleksandr S.; Namashivaya, Siva S. R.; Khrustalev, Victor N.; Hampel, Frank; Laikov, Dimitri N.; Kataev, Evgeny (Journal of Organic Chemistry, 2020)
Control of isomerization of a receptor bearing multiple light-switchable subunits in a confined space is critical for the design of synthetic molecular machines. Toward this goal, a new azacryptand containing three azobenzene subunits has been developed, and its photoisomerization in an aqueous solution has been studied depending on anion coordination and recognition by a larger host-cucurbit[8]uril (CB[8]). The cryptand in its hexaprotonated form shows considerable affinity for fluoride and perchlorate, which in turn affects the isomer distribution of the receptor under UV-light irradiation, stabilizing the isomers of the cryptand with Z-configurations. CB[8] was found to be able to encapsulate the isomers of the cryptand by forming a Matryoshka-type complex. The irradiation of a 10:1 CB[8]-cryptand mixture has led to a selective conversion of the cryptand to the E,E,Z isomer inside CB[8]. It has been demonstrated that the addition of fluoride to the resulted complex induces the release of the cryptand as a major E,E,E isomer, while other studied anions were ineffective in this reaction. To our knowledge, this work presents a first example of a host-controlled photoisomerization of an anion receptor bearing multiple switching azobenzenes that model the function of naturally occurring chaperones.
CRIS-Team WoS Importer:2020-08-07

Converting pH probes into “turn-on” fluorescent receptors for anions - Kataev, Evgeny (Chemical Communications, 2023)
Recognition of anions by synthetic receptors is an integral part of supramolecular chemistry continuing to expand and find new application areas in our daily life. Many applications require visualization of anion recognition events, and the generated analytical signal is used to quantify anions in solution. Transferring a binding event to a measured signal is a challenging task. The design of a synthetic receptor must involve not only the perfectly positioned binding sites with complementary noncovalent interactions for a guest but should also realize the sensing mechanism that generates a strong analytical response upon guest binding. This feature article outlines the design concept for the construction of “turn-on” fluorescent receptors for anions involving fluorescent pH probes. Applications of this concept for the construction of synthetic fluorescent receptors for inorganic anions and nucleotides are described. Features of the obtained receptors and possible competing binding and sensing processes in solution are analyzed to understand the scope and limitations of the approach.
CRIS-Team Scopus Importer:2023-02-10

Cytosine-Functionalized Macrocyclic Receptor for Nucleotides: Combining Three Recognition Motifs - Morozov, Boris; Oshchepkov, Aleksandr; Xu, Dan; Kataev, Evgeny (European Journal of Organic Chemistry, 2023)
Nucleoside monophosphates perform various essential functions and serve as second messengers in living systems. Despite the success of nucleotide-selective probes based on proteins, the creation of synthetic receptors for nucleoside monophosphates remains a challenging task. In this paper, we explore the design of synthetic receptors based on a combination of three recognition motifs. We show that each binding motif contributes to the formation of the host-guest complexes. The core macrocycle provides recognition of the phosphate residue of the nucleotide, while naphthalimide and the attached cytosine residue participate in the coordination of the nucleobase via π-π and hydrogen bonding interactions. The presence of cytosine in the receptor structure substantially increases the overall affinity of receptors for nucleotides. A considerable increase (100-fold) in binding affinities is observed for the tetranucleotide DNA sequences 5′-GGGG -3′ and 5′-CCCC-3′, as compared to the previously reported system without the attached cytosine.
CRIS-Team Scopus Importer:2023-12-15
Keywords: anion sensing; cyclic di-GMP; guanosine; naphthalimide; nucleotide recognition

Dye-functionalized phosphate-binding macrocycles: from nucleotide to G-quadruplex recognition and "turn-on" fluorescence sensing - Oshchepkov, Aleksandr; Reznichenko, Oksana; Xu, Dan; Morozov, Boris; Granzhan, Anton; Kataev, Evgeny (Chemical Communications, 2021)
A novel strategy to design "turn-on" fluorescent receptors for G-quadruplexes of DNA is presented, which relies on the connection of phosphate binding macrocycles (PBM) with naphthalimide dyes. A new PBM-dye family was synthesized and evaluated in terms of binding and detection of nucleotides and DNA G-quadruplexes of different topologies.
CRIS-Team WoS Importer:2021-10-08

Effects of Ring Functionalization in Anthracene-Based Cyclophanes on the Binding Properties Toward Nucleotides and DNA - Basaran, Ismet; Agafontsev, Aleksandr; Morozov, Boris; Oshchepkov, Alexander S.; Imhof, Petra; Kataev, Evgeny (Chemistry - A European Journal, 2024)
Supramolecular recognition of nucleobases and short sequences is an emerging research field focusing on possible applications to treat many diseases. Controlling the affinity and selectivity of synthetic receptors to target desired nucleotides or short sequences is a highly challenging task. Herein, we elucidate the effect of substituents in the phenyl ring of the anthracene-benzene azacyclophane on the recognition of nucleoside triphosphates (NTPs) and double-stranded DNA. We show that introducing phenyl rings increases the affinity for NTPs 10-fold and implements groove and intercalation binding modes with double-stranded DNA. NMR studies and molecular modeling calculations support the ability of cyclophanes to encapsulate nucleobases as part of nucleotides.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Cyclophanes; Fluorescence sensing; Nucleotide; Recognition; π–π interaction

Fluorescence detection of phosphonates in water by a naphthalimide-based receptor and its derived cryopolymers - Oshchepkov, Aleksandr; Oshchepkov, Maxim; Kamagurov, Semen; Redchuk, Anatoly; Oshchepkova, Margarita; Popov, Konstantin; Kataev, Evgeny (New Journal of Chemistry, 2020)
Phosphonates have found broad commercial applications as scale inhibitors in reverse osmosis facilities, boilers, heat exchangers, evaporation plants, and oilfields. Irrespective of their long-term use, there is a cogent need to detect phosphonates in aqueous solution "online" to control their actual concentration in industrial water treatment. Towards this goal, a novel fluorescent-labeled monomerMcontaining a triamine subunit and 1,8-naphthalimide with an allyl group has been synthesized and found to exhibit a selective fluorescence enhancement with phosphonates in the presence of other anions. The absorption and fluorescence properties ofMas well as its effective stability constants with various phosphonates have been studied in a wide pH range.Mhas been implemented in the synthesis of cryopolymers, which can detect phosphonates in aqueous solution. The presented results provide an important contribution to the future design of fluorescent polymer probes for antiscalants.
CRIS-Team WoS Importer:2020-08-07

Fluorescent macrocycle-dye-anchor conjugates for sensing phospholipids in biomembranes - Oshchepkov, Alexander S.; Cruz Da Silva, Elisabete; Morozov, Boris; Aparin, Ilya O.; Kataev, Evgeny; Klymchenko, Andrey S. (Sensors and Actuators B-Chemical, 2023)
Negatively charged phospholipids can serve as biomarkers for a number of biological processes allowing detection of apoptosis in animal cells, drug-induced phospholipidosis as well as detection of bacteria. Selective detection of phospholipids thus represents an important but challenging goal. The development of fluorescent probes capable of selective recognition of specific phospholipids can be a promising solution to the problem. Along this line, we have developed the macrocycle-dye-anchor conjugates, in which the macrocycle recognizes the phosphate residue, hydrocarbon anchors ensure hydrophobic interaction with the membrane, and environment-sensitive fluorescent dye functions as a reporter unit. To the best of our knowledge, this is the first report of synthetic fluorescent probes for specific phospholipids using the macrocycle-dye-anchor concept. We have studied the effect of the structure of the anchor and the macrocycle on the resulting fluorescent response in the presence of two types of lipid vesicles: phosphatidylcholine as a model of healthy cells and phosphatidylcholine and phosphatidylserine (1:1), mimicking apoptotic cells. The properties of the obtained compounds were analyzed in various model media and in HeLa cells. The response of fluorescent probes has been found to be strongly dependent on the macrocycle structure, length of the anchor, nature of the buffer, and pH. The probes showed significant fluorescence enhancement in apoptotic cells, thus providing the proof of concept for the macrocycle-dye-anchor design.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Anion recognition; Anion sensing; Fluorescence imaging; Membrane probes; Naphthalimide; Phospholipids

Helix-Like Receptors for Perrhenate Recognition Forming Hydrogen Bonds with All Four Oxygen Atoms - Morozov, Boris; Ravi, Anil; Oshchepkov, Aleksandr; Rueffer, Tobias; Lang, Heinrich; Kataev, Evgeny (Chemosensors, 2021)
Supramolecular recognition of perrhenate is a challenging task due to therelatively large size and low charge density of this anion. In this work, we design and synthesize a family of helix-like synthetic receptors that can bind perrhenate by forming hydrogen bonds with all four oxygen atoms of the anion. Among the investigated rigid helix-forming subunit derived from 1,1 '-ferrocenedicarboxylic acid, 1,3-phenylenediacetic acid and 2,2 '-(ethyne-1,2-diyl)dibenzoic acid, the latter one shows the best selectivity for perrhenate recognition. However, the receptor based on 1,1 '-ferrocenedicarboxylic acid demonstrates selectivity to bind chloride in a 1:2 fashion. The properties of the receptors are investigated in the acetonitrile solution by using NMR, UV-Vis, and in the solid state by single crystal X-ray analysis.
CRIS-Team WoS Importer:2021-06-04

Host-Guest Systems on the Surface of Functionalized Superparamagnetic Iron Oxide Nanoparticles (SPIONs) Utilizing Hamilton Receptors and Cyanurate Derivative Molecules - Ali, Muhammad; Kataev, Evgeny; Müller, Johannes; Park, Hyoungwon; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2021)
The study of hydrogen bonding interactions at the level of functionalized nanoparticles remains highly challenging and poorly explored area. In this work, superparamagnetic iron oxide nanoparticles (SPIONs) were orthogonally functionalized using receptors bearing multiple hydrogen bonding motifs. Pristine SPIONs were modified by wet chemical processes with Hamilton receptors (hosts), or cyanurate-guest molecules linked to phosphonic acid moieties for monolayer functionalization. The modified surfaces were fully characterized and the number of attached ligands on the surface were determined. The host-guest interactions on the interface of modified SPIONs were investigated by using UV-Vis spectroscopic titrations. Functionalized SPIONs demonstrated two to three magnitudes stronger binding affinities as compared to the related molecular interactions in solution due to synergistic effects on complex surface environment. Higher supramolecular binding ratios of host-guest interactions on the modified surface were emerged. These studies provide fundamental insights into supramolecular complexations on the surface at solid-liquid interface systems with applications in engineered nanomaterials, nano-sensing devices, and drug delivery systems.
CRIS-Team Scopus Importer:2021-11-05
Keywords: artificial hydrogen bonds; functionalized nanoparticles; hamilton receptors; host-guest chemistry; SPIONs

Macrocyclic Conformational Switch Coupled with Pyridinium-Induced PET for Fluorescence Detection of Adenosine Triphosphate - Morozov, Boris; Gargiulo, Fabiano; Ghule, Swapnil; Lee, Dong Joon; Kim, Hwan Myung; Kataev, Evgeny (Journal of the American Chemical Society, 2024)
The binding of nucleotides is crucial for signal transduction as it induces conformational protein changes, leading to downstream cellular responses. Synthetic receptors that bind nucleotides and transduce the binding event into global conformational rearrangements are highly challenging to design, especially those that operate in an aqueous solution. Much work is focused on evaluating functionalized dyes to detect nucleotides, whereas coupling of a nucleotide-induced conformational switching to a sensing event has not been reported to date. We disclose synthetic receptors that undergo a global conformational rearrangement upon nucleotide binding. Integrating naphthalimide and the pyridinium ion into the structure enables stabilization of the folded conformation and efficient fluorescence quenching. The binding of a nucleotide rearranges the receptor conformation and alters the strong fluorescence enhancement. The methylpyridinium-containing receptor demonstrated high sensing selectivity for adenosine 5′-triphosphate (ATP) and a record 160-fold fluorescence enhancement. It can detect fluctuations of ATP in HeLa cells and possesses low cytotoxicity. The developed systems present an attractive approach for designing ATP-responsive artificial molecular switches that operate in water and integrate a strong fluorescence response.<br

Mesoporous supraparticles with a tailored solid-liquid-gas interface for visual indication of H2 gas and NH3 vapours - Zink, Andreas; Reichstein, Jakob; Ruhland, Nico; Stockinger, Nina; Morozov, Boris; Cuadrado Collados, Carlos; Thommes, Matthias; Kataev, Evgeny; Wintzheimer, Susanne; Mandel, Karl (Chemical Communications, 2024)
Dual-gasochromic supraparticles that undergo rapid eye-readable and gas-specific colour changes upon reaction with hydrogen or ammonia are reported. This functionality is achieved by tailoring the solid-liquid-gas interface within the mesoporous framework of supraparticles via spray-drying.
CRIS-Team Scopus Importer:2024-06-14

Micromolar Affinity and Higher: Synthetic Host-Guest Complexes with High Stabilities - Sarkar, Sayan; Ballester, Pablo; Spektor, Mark; Kataev, Evgeny (Angewandte Chemie International Edition, 2023)
The design of high-affinity synthetic host-guest complexes is of paramount importance because they are key elements in constructing unprecedented supramolecular assemblies, functional materials, molecular probes, artificial signal transduction events, and interfaces with the biological world. The present review article collects recent achievements in the design of 1 : 1 host-guest complexes with outstanding stabilities, i.e., exceeding 10(6) M-1. The relationships between the measured thermodynamic constants and the structural parameters of the interacting species are analyzed. The design features of high-affinity hosts are discussed in light of their binding properties. Different solvents and different types of noncovalent interactions are considered for the stabilization of the complexes. Finally, some hints are provided for the design of future synthetic receptors displaying high affinity and selectivity.
CRIS-Team WoS Importer:2023-05-26

Naphthalimide-Based Fluorescent Polymers for Molecular Detection - Oshchepkov, Aleksandr S.; Oshchepkov, Maxim S.; Oshchepkova, Margarita V.; Al-Hamry, Ammar; Kanoun, Olfa; Kataev, Evgeny (Advanced Optical Materials, 2021)
The beginning of the 21st century was marked by the intensive development of fiber-optic sensors. New functional materials with excellent sensory properties are required to design such sensors. Fluorescent probes for neutral and charged molecules are constantly developing. However, only a small part of the reported probes was successfully converted into functional sensing polymers and found real-world applications. A great challenge is to retain the sensing properties of a probe in a polymer matrix. The purpose of this review is to understand how properties of a probe are changed upon incorporation into a polymer and to reveal successful approaches. The review focuses on the use of the naphthalimide-based probes in the construction of sensing polymers. The literature overview is presented according to the nature of the guest molecules targeted for the quantitative detection: cations, anions, and small organic molecules.
CRIS-Team Scopus Importer:2021-02-26
Keywords: fiber-optic sensor; fluorescence; fluorescent polymer; molecular probe; naphthalimide

Naphthalimide-Buckybowl Tweezer for Selective Recognition of Fullerene C70 - Ghule, Swapnil; Korenkov, Konstantin O.; Sharapa, Dmitry I.; Amsharov, Konstantin Y.; Kataev, Evgeny; Oshchepkov, Alexander S. (Chemistry - A European Journal, 2025)
Supramolecular tweezers-like receptors represent a simple and efficient approach for the molecular recognition of fullerenes. Straightforward synthesis and easy fine-tuning of their geometry are the advantages that allow one to achieve strong binding and specific selectivity. However, the use of buckybowls in constructing tweezers and incorporating fluorescent dyes is still underexplored. To achieve this goal, we have designed mono- and di-substituted receptors by attaching indacenopicene to a naphthalimide dye. The tweezers-like receptor shows the highest selectivity for C70 with an affinity of 2150 M−1, which is about 50-fold stronger than the recognition of C60. DFT and NMR data indicate that the preferred binding mode involves the ellipsoidal C70 molecule coordinating with buckybowls at its poles. In this arrangement, the naphthalimide core establishes two CH–π interactions with the fullerene. The results indicate that conjugating buckybowls with naphthalimides in a suitable design presents a promising method for selective binding and fine-tuning photoinduced electron transfer in the host–guest complex.
CRIS-Team Scopus Importer:2025-04-11
Keywords: buckybowl; dispersion interactions; fullerene; molecular tweezers; naphthalimide

Naphthalimide-functionalized bisphosphonates for fluorescence detection of calcification in soft tissues - Oshchepkov, Aleksandr; Oshchepkov, Maxim; Pavlova, Galina; Ryabova, Anastasiya; Kamagurov, Semen; Tkachenko, Sergei; Frolova, Svetlana; Redchuk, Anatoly; Popov, Konstantin; Kataev, Evgeny (Sensors and Actuators B-Chemical, 2020)
Novel naphthalimide-functionalized bisphosphonates with different spacer length have been designed and synthesized. The spectroscopic properties, dissociation constants and complexation behavior with calcium(II) have been studied in aqueous solution. It has been shown that the length of the spacer has a dramatic effect on the fluorescence, Ca2+ binding properties and solubility of Ca2+ complexes in aqueous solution. New fluorescent bisphosphonates have been found to provide a perfect contrasting of inorganic industrial fouling (barite) and human tissue calcification (hydroxyapatite). The affinity of the fluorescent bisphosphonates for the bone matrix in the presence of human fibroblast cells has been tested in vitro with hydroxyapatite crystals imitated the human bone. Microscopic fluorescence analysis has demonstrated that fluorescent bisphosphonates are able to bind efficiently and selectively to the hydroxyapatite in the presence of human fibroblast cells.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Antiscalants; Bisphosphonates; Fluorescent dye; Naphthalimide; Soft tissue calcification

Ratiometric Detection of ATP by Fluorescent Cyclophanes with Bellows-Type Sensing Mechanism - Agafontsev, Aleksandr M.; Shumilova, Tatiana A.; Oshchepkov, Aleksandr S.; Hampel, Frank; Kataev, Evgeny (Chemistry - A European Journal, 2020)
Pyrene-based cyclophanes have been synthesized with the aim to realize a bellows-type sensing mechanism for the ratiometric detection of nucleotide concentrations in a buffered aqueous solution. The sensing mechanism involves the encapsulation of a nucleobase between two pyrene rings, which affects the monomer-excimer equilibrium of the receptor in the excited state. The nature of the spacer and its connection pattern to pyrene rings have been varied to achieve high selectivity for ATP. The 1,8-substituted pyrene-based cyclophane with the 2,2’-diaminodiethylamine spacer demonstrates the best selectivity for ATP showing a 50-fold increase in the monomer-excimer emission ratio upon saturation with the nucleotide. The receptor can detect ATP within the biological concentrations range over a wide pH range. NMR and spectroscopic studies have revealed the importance of hydrogen bonding and stacking interactions for achieving a required receptor selectivity. The probe has been successfully applied for the real-time monitoring of creatine kinase activity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: cyclophane; fluorescence sensing; host-guest chemistry; macrocycle; nucleotide recognition

Supramolecular Recognition of Cytidine Phosphate in Nucleotides and RNA Sequences - Morozov, Boris; Oshchepkov, Aleksandr S.; Klemt, Insa; Agafontsev, Aleksandr; Krishna, Swathi; Hampel, Frank; Xu, Honggui; Mokhir, Andriy; Guldi, Dirk Michael; Kataev, Evgeny (JACS Au, 2022)
Supramolecular recognition of nucleotides would enable manipulating crucial biochemical pathways like transcription and translation directly and with high precision. Therefore, it offers great promise in medicinal applications, not least in treating cancer or viral infections. This work presents a universal supramolecular approach to target nucleoside phosphates in nucleotides and RNA. The artificial active site in new receptors simultaneously realizes several binding and sensing mechanisms: encapsulation of a nucleobase via dispersion and hydrogen bonding interactions, recognition of the phosphate residue, and a self-reporting feature─“turn-on” fluorescence. Key to the high selectivity is the conscious separation of phosphate- and nucleobase-binding sites by introducing specific spacers in the receptor structure. We have tuned the spacers to achieve high binding affinity and selectivity for cytidine 5′ triphosphate coupled to a record 60-fold fluorescence enhancement. The resulting structures are also the first functional models of poly(rC)-binding protein coordinating specifically to C-rich RNA oligomers, e.g., the 5′-AUCCC(C/U) sequence present in poliovirus type 1 and the human transcriptome. The receptors bind to RNA in human ovarian cells A2780, causing strong cytotoxicity at 800 nM. The performance, self-reporting property, and tunability of our approach open up a promising and unique avenue for sequence-specific RNA binding in cells by using low-molecular-weight artificial receptors.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cytosine; encapsulation; fluorescence sensing; nucleotide recognition; synthetic receptors

Three-state fluorescence hydrochromism of a fluorophore-spacer-receptor system with variations in relative humidity - Ni, Yanhai; Han, Yishan; Kataev, Evgeny; Olson, Mark A. (Chemical Communications, 2022)
The uptake of atmospheric moisture by hygroscopic materials can have marked effects on a material's physical and chemical properties. This is true of materials that go on to incorporate waters of hydration in their molecular structural lattice, forming stable hydrates with fluctuations in relative humidity (RH). Nevertheless, RH remains relatively uncontrolled for a variable that can fluctuate widely depending on geographical climate, weather fluctuations, and building HVAC system stability. Herein, we report a processable 1,8-napthalimide-based fluorophore-spacer-receptor system that unexpectedly exhibited reversible three-state fluorescence hydrochromism with changes in RH due to RH-induced solid state molecular rearrangement. Care should be taken to evaluate the impact of variations in RH when characterising the solid state emission properties of charged fluorescent materials.
CRIS-Team Scopus Importer:2022-12-02

Triazatriangulenium salts - hosts and guests in supramolecular assemblies in solution - Sarkar, Sayan; Böck, Michael; Uhl, Agnes; Agafontsev, Aleksandr; Schatz, Jürgen; Kataev, Evgeny (Organic Chemistry Frontiers, 2024)
Self-assembly of triazatriangulenium dyes (TATA) bearing C3-C8 substituents and their interaction with aromatic compounds were studied. The dyes with alkyl chains longer than C5 were strongly aggregated in solution, while those with shorter alkyl chains formed hetero-stacks with aromatic compounds in chloroform. Anthracene, pyrene, coronene, and a naphthalene diimide dye formed heterostacks in solution with association constants 104 M−1. Anthracene and pyrene-based water-soluble cyclophanes were designed to investigate host-guest complexes with TATA dyes in an aqueous solution. Experimental and theoretical investigations suggest that only pyrene-based cyclophane is able to encapsulate TATA dyes. These self-assembled structures constitute new supramolecular motifs to construct multilayered organic structures.
CRIS-Team Scopus Importer:2024-04-26